GC-MS Metabolite Profiling and Chemometric Analysis of Robusta Green Beans (Bantjah Coffee) - Permatasari, Fitria Indah; Nazir, Novizar; Anggraini, Tuty; Hellyward, James; Techavuthiporn, Chairat; Syukri, Daimon (My University, 2025)
In this study, three types of Robusta green bean coffee developed in the Bantjah area were characterized. This study characterized three types of Robusta green coffee beans with potential for development in the Bantjah area. The three coffee beans were (A) Bantjah area and the two (B, C) selected from different altitudes of the West Sumatra area. The purpose of this study was to analyze metabolite profiling of Robusta green coffee green beans. The coffee beans were fermented using the natural method and then the extract was derivatized with N-Methyl-N-(trimethylsilyl) trifluoroacetamide before being analyzed by Gas chromatography-mass spectrometry (GCMS). The chromatogram obtained was then analyzed statistically using principle component analysis (PCA). GCMS analysis produced more than 60 chemical components in green beans of Robusta coffee. Principle component analysis determined the metabolite distribution of coffee samples as influenced by their geographical origin. Coffee originating from the highlands had different marker compounds than coffee grown in lower plains. A metabolomics approach provides a comprehensive explanation of this relationship.
Keywords: Agroecology; aroma; caffeine; highlands; metabolomics; PCA